Pengelolaan Hulu Sub-DAS Logawa dalam Perda Penataan Ruang Kabupaten Banyumas - Budi Prabowo As'attohara; Imam Santosa; Tamad Tamad (Jurnal Wilayah dan Lingkungan, 2021)
The watersheds upstream degradation in Java, is alarming and trigger changes to overall hydrological character of watersheds and its ecosystem services. Maintaining healthy watershed from future degradation can be initiated by a means formulating policies and designing appropriate management plan. The Logawa sub-watershed is not a critical watershed, nonetheless the upstream is part of mountain slope with very high annual rainfall. The headwater of Logawa sub-watershed plays an important role in catching annual rainfall and provide the underground and surface water supply for Kota Purwokerto. It is important to study the government's regulation related on its management, to determine the current management policy. This study aims to analyze the district level spatial and regional planning regulation related to the upstream management of the Logawa Sub-watershed. When this study was conducted, Local Government Regulation Number 10 year of 2011, concerning regional spatial planning was the only regulation of the Banyumas district that could regulate management of the upstream zone of Logawa sub-watersheed. This spatial regulation assign the upstream area of the Logawa sub-watershed as conservation zone, as well as the development area for generating electricity and river tourism, but does not specifically stipulate a minimum conservation zone forest land cover. The regulation is not sufficient for managing healthyness of the upstream Logawa Sub-watershed for the future, as well as to manage the upstream zone of the Logawa Sub-watershed as an upstream watershed ecosystem.